A Scaffold‐Diversity Synthesis of Biologically Intriguing Cyclic Sulfonamides. Issue 68 (7th November 2019) - Zimmermann, Stefan; Akbarzadeh, Mohammad; Otte, Felix; Strohmann, Carsten; Sankar, Muthukumar Gomathi; Ziegler, Slava; Pahl, Axel; Sievers, Sonja; Kumar, Kamal
Abstract: A "branching–folding" synthetic strategy that affords a range of diverse cyclic benzo‐sulfonamide scaffolds is presented. Whereas different annulation reactions on common ketimine substrates build the branching phase of the scaffold synthesis, a common hydrogenative ring‐expansion method, facilitated by an increase of the ring‐strain during the branching phase, led to sulfonamides bearing medium‐sized rings in a folding pathway. Cell painting assay was successfully employed to identify tubulin targeting sulfonamides as novel mitotic inhibitors. Abstract : Branch, fold and paint ! A "branching–folding" synthetic strategy delivers a range of diverse cyclic benzo‐sulfonamides and a cell painting analysis led to disclose novel tubulin targeting sulfonamide mitotic inhibitors.